THE PERSON-CENTERED APPROACH: ANALYSIS AND DESCRIPTION - Saodat Khamidovna Gayupova (Galaxy International Interdisciplinary Research Journal, 2023)
This article highlights the advantages of the person-centered approach, which is considered a modern pedagogical approach, and its differences from the traditional education. A comparative analysis of traditional and person-centered approach to education.